Sinyal kinerja keuangan sebelum dan sesudah pencabutan status darurat pandemi COVID-19 - Dwiki Rama Sbastian; Pontoh, Winston; Tangkuman, Steven Josia (Manajemen Bisnis dan Keuangan Korporat, 2024)
Financial performance is a measure that definitively assesses how healthy and efficient a company is in managing its resources. This research will determine whether there are differences and correlations in earnings quality, profitability, and leverage, which indicator of financial performance, before and after the revocation of the COVID-19 pandemic emergency status in 2023 for companies with large market capitalizations on the Indonesia Stock Exchange. This thesis employs a quantitative analytical method with a comparative-associative approach to identify differences and relationships. This study employs two analytical tools: the Mann-Whitney Test and Spearman's correlation test. The results clearly show that there are no significant differences or correlations in earnings quality, return on assets, or debt to assets ratio before and after the revocation of the emergency status. However, there is a significant negative correlation between the debt to assets ratio and return on assets before and after the revocation of the 2023 emergency status.